Numerical modeling of the temperature fields in a semi-confined enclosure heated by a linear heat source. (November 2020) - Kouéni-Toko, C.A.; Tcheukam-Toko, D.; Kuitche, A.; Patte-Rouland, B.; Paranthoën, P.
Abstract: The objective of this work is to carry out the numerical computation of the temperature fields in a semi-ventilated enclosure of aspect ratio H/R   =  2476 having at its base a linear and centered heat source of length l 1  = 200 mm and of diameter D  = 20 mm. The enclosure has a length L  = 210 mm width l  = 210 mm and height H  = 520 mm. It communicates with the outside through 20 openings located at the bottom of the enclosure. These openings are distributed in equal number (10) on the left and right walls in the direction (0 x ). Each opening has a diameter d  = 4 mm. At the heat source we imposed a temperature Δ T 0 which is observed. Three (03) numbers of Raleigh reduced Ra* = 9, 74 × 10 7, Ra* = 1, 61 × 10 8, Ra* = 2, 05 × 10 8 . Correspond to three (03) values of Δ T 0, 40 K, 60 K and 75 K. To solve the equations of the physical phenomenon, we used direct numerical simulation (DNS) as a simulation technique. It is based on the finite volume method. The discretization of equations gives a system of algebraic equations whose solution allows us to determine the fields of all the variables of the problem considered. The SIMPLE algorithm was used for correction of pressure on a non-uniform mesh. As discretization scheme, we used the QUICK scheme for solving the equations of momentum and energy conservations. And schema "Body Strength weighted for the resolution of the pressure. The results show that the cool air at room temperature enters the enclosure through the openings located near the floor and the warm air at higher temperature than the outside temperature leaves through the openings located near the height h/H . From the height z+ = 0 to z+ < 0, 5, a vertical thermal gradient is observed between the positions x+ = 0 and x+ = −0, 5 and 0, 5 . For the values of z+ between 0, 5 and 1, the interior of the enclosure is hot, almost homogeneous and higher temperature than the outside. The air movements in the enclosure and at the openings are created by the thermal plume. The comparison of these results with the experimental and numerical results case 11 of Koueni Toko (2019) that shows the phenomenons are similar almost. But with a thermal plume more hot. And of elevated more temperature values in the upper area of the enclosure. This difference may be due to the size and number of openings.